The Implementation of Self Congruency Theory on Online Impulse Buying Intentions Mediated by Consumer Confidence in Online Shopping Towards Gen-Z - Linda Anadya Tastya; Yolanda Masnita Siagian; Husna Leila Yusran (International Journal of Marketing & Human Resource Research, 2026)
This research focuses on Online Impulse Buying Intentions, defined as the motivation to purchase items without planning while browsing online sites, often triggered by product recommendations. The study employs the Self-Congruency Theory framework, which explains how the alignment between consumer identity and perceptions of influencers or products facilitates impulsive behavior. A contradiction exists in the literature regarding the relationship between Influencer–Product Congruence and Online Impulse Buying Intentions: some studies find a direct influence, while others do not. To address this, a research model was developed to test the influence of Consumer – Influencer Congruence, Consumer – Product Congruence, and Influencer – Product Congruence on Online Impulse Buying Intentions. This model integrates Wishful Identification as a moderating variable and Consumer Confidence in Online Shopping as a mediating variable. The main contribution of this study is to expand the theoretical model by incorporating Consumer Confidence in Online Shopping as a mediating variable. This addition aims to provide comprehensive insights into the psychological mechanisms underlying impulsive behavior in online shopping. These findings suggest that direct congruence between the consumer and the influencer, and between the consumer and the product, is a strong driver of Online Impulse Buying Intentions. The recommendation is that marketers should focus on creating strong congruence between consumer values and the influencer’s image, as well as product suitability with the consumer's lifestyle, as these factors directly trigger Online Impulse Buying Intentions